2009
DOI: 10.1186/bcr2345
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer-associated metastasis is significantly increased in a model of autoimmune arthritis

Abstract: IntroductionSites of chronic inflammation are often associated with the establishment and growth of various malignancies including breast cancer. A common inflammatory condition in humans is autoimmune arthritis (AA) that causes inflammation and deformity of the joints. Other systemic effects associated with arthritis include increased cellular infiltration and inflammation of the lungs. Several studies have reported statistically significant risk ratios between AA and breast cancer. Despite this knowledge, av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 52 publications
(47 reference statements)
4
71
0
2
Order By: Relevance
“…Systemic inflammation has been associated with an increased risk of breast cancer development (Gadalla et al, 2009) and metastasis (Das Roy et al, 2009). In addition, local inflammation leading to chronic mastitis in the mammary gland occurred at a higher frequency and earlier time point of tumour development in the ATX and LPA receptor transgenic mice .…”
Section: Breast Cancer Progression May Involve Lpa-induced Cytokine Pmentioning
confidence: 99%
“…Systemic inflammation has been associated with an increased risk of breast cancer development (Gadalla et al, 2009) and metastasis (Das Roy et al, 2009). In addition, local inflammation leading to chronic mastitis in the mammary gland occurred at a higher frequency and earlier time point of tumour development in the ATX and LPA receptor transgenic mice .…”
Section: Breast Cancer Progression May Involve Lpa-induced Cytokine Pmentioning
confidence: 99%
“…[14][15][16] A previous study has shown that the incidence of breast cancer associated lung metastasis is significantly higher in mice with arthritis. 17 Moreover, celecoxib, an anti-inflammation drug, significantly reduces metastasis to lungs. 18,19 These findings indicate the correlation between inflammatory microenviroment and the homing of circulating tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Si bien Cx ha sido previamente reportado su acción frente a metástasis pulmonar (Gendy et al, 2011;Barlow et al, 2012;Zhang et al, 2014) y hueso (Das Roy et al, 2009), y frente a apoptosis y crecimiento tumoral en el mismo modelo (Rosas et al, 2014); no hay información de su efecto frente a metástasis pulmonar cuando es asociado a micropartículas de PLGA.…”
Section: Discussionunclassified